Kinerja dan kinetika produksi biohidrogen secara batch dari sampah buah melon dalam reaktor tangki berpengaduk - Febrina Sarlinda; Sarto Sarto; Muslikhin Hidayat (Jurnal Rekayasa Proses, 2018)
Melon fruit waste with high sugar and water content is potential as a substrate for hydrogen production by dark fermentation. This study investigated the performance of biohydrogen production from melon fruit waste in a stirred tank reactor with initial concentration of 13100 mg sCOD/L, in room temperature, initial pH of 7 and controlling final pH at 5.5 by adding NaOH. The fermentation was carried out for 24 hours. The value of pH, volatile solid (VS), soluble chemical oxygen demand (sCOD), volatile fatty acid (VFA), biogas volume, hydrogen content, and cell concentration was analized every hour to determine the performance of reactor. Hydrogen content reached 16.20% with hydrogen production rate (HPR) of 458.12 mL/Lreactor/day in the standard temperature and pressure (STP) condition. Substrate consumption at the end of fermentation reached 24.61% of sCOD and 78.28% of VS. Metabolite products were dominated by acetate and butyrate with butyrate to acetate ratio of 7:6. The kinetic of product formation was evaluated by the kinetic model of Gompertz. Meanwhile the kinetics of cell growth was approximated by logistics model.